Prototipe SIMHEC sebagai Media Simulasi Penjahitan Luka pada Mahasiswa - Yessi Azwar; Salma Asilah; Nabila Sabri Effendi Putri; Ummu Aiza; Dina Apriana; Tina Permata Sari; Rahmadini Maharani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Learning wound suturing abilities is a key asset for healthcare students, particularly midwifery and nursing students. However, inadequate simulation media sometimes inhibits the practical learning process. This study intends to investigate the usefulness of the SIMHEC prototype as a wound suturing simulation medium in boosting student knowledge. The research approach employed was a pre-experimental study with a one-group pretest-posttest design. The study involved 30 healthcare students as respondents. The research instrument was a 10-item multiple-choice questionnaire administered before (pretest) and after (posttest) use of the SIMHEC prototype. The results showed a rise in the average score, from 85 in the pretest to 100 in the posttest. This implies that employing the SIMHEC prototype as a wound suturing simulation medium can assist increase students' understanding and skills in the learning process. Therefore, the SIMHEC prototype is considered effective and can be used as an alternate learning medium for midwifery and nursing students.